AN EXPERIENCE OF PERCUTANEOUS TRACHEOSTOMY IN TWENTY OBESITY PATIENTS WITH SHORT NECK IN A TERTIARY CARE HOSPITAL IN PAKISTAN: An Experience of Percutaneous Tracheostomy - Asad, Muhammad; Haq, Muhammad Ehsan-ul-; Ali, Liaquat; Rao, Zahid Akhtar (Pakistan Armed Forces Medical Journal, 2008)
Objective: To evaluate the success rate, procedure time and per-operative complications of percutaneous dilational tracheostomy in obese patients with short neck. Design: Case series, descriptive study. Place and duration of study: Military Hospital Rawalpindi, from Jan 2006 to July 2007. Patients and Methods: Twenty obese patients with short neck were referred from intensive care unit (ICU) to operation theatre for open surgical tracheostomy (ST). Before doing open procedure, all the patients were reassessed and an attempt was made by a team of experienced ENT surgeon and anaesthetist, to do percutaneous dilational tracheostomy (PDT) as first option. The success rate, procedure time and per-operative complications were noted. Data was collected over a period of one and half year. Results: Twenty patients (12 F and 8 M), mean age 53 (34-80) years, mean body mass index (BMI=40) (34-45) were studied. The successful PDT was performed in 18 patients and in two patients procedure was converted to open surgical tracheostomy. Average time taken was 15 min. per-operative complications noted were, false passage, bleeding and leakage of air due to cuff puncture. Conclusion: In obese patients with short neck, if percutaneous dilational tracheostomy is performed by an experienced operator, in operation theatre (OT) with full preparation, good light and proper positioning, the procedure can be performed with in 15 min, the success rate is high with little complications.